Learning from and Reacting to School Inspection – Two Swedish Case Narratives. Issue 1 (2nd January 2018) - Segerholm, Christina; Hult, Agneta
ABSTRACT: Throughout Europe, school inspection has become a visible means of governing education. This education and inspection policy is mediated, brokered, interpreted, and learned through networked activities where the global/European meet the national/local, giving national and local "uptake" a variety of characteristics. We explore the local features of this "uptake" as processes of learning in the interaction between schools and inspectors in Sweden. Drawing theoretically on Jacobsson's notion of governing as increasingly done through meditative activities and on Leontiev's activity theory, we suggest that school actors learn compliance through diverse emotions provoked by inspection processes in different local settings. Based on observations of inspections, interviews with teachers, head teachers and inspectors, documents, reports, and decisions, we portray how governing education is done through inspection processes in two Swedish schools. The case narratives underscore the importance of local context in these governing and learning processes.